Internationalization of Young Firm Using Internet Technology: Case of Google - Azlini, Awang (2009)
A growing phenomenon in issue in internationalization of the young firm that use the internet as a channel offering products or service. Purpose of this study was to see that young firms can succeed by using internet technology as channel to access the certain country through this internationalization. This study use the Theory of Internationalization and Theory of New Venture which proved that firm will can succeed in brief periods if use technology internet as medium or mode of entry in internationalization. By using by take example Google Company as case study basis, with perception that internet use technology overall at all those countries being participated, can show one firm will succeed quickly if use internet as medium in his mode of entry. Here it is clear that, theory used by very helpful researcher in this study because in fact, too helpful technology internet new firms in entering international market.